2013
DOI: 10.1016/j.virol.2013.08.022
|View full text |Cite
|
Sign up to set email alerts
|

The multifaceted effect of PB1-F2 specific antibodies on influenza A virus infection

Abstract: PB1-F2 is a small influenza A virus (IAV) protein encoded by an alternative reading frame of the PB1 gene. During IAV infection, antibodies to PB1-F2 proteins are induced. To determine their function and contribution to virus infection, three distinct approaches were employed: passive transfer of anti-PB1-F2 MAbs and polyclonal antibodies, active immunization with PB1-F2 peptides and DNA vaccination with plasmids expressing various parts of PB1-F2. Mostly N-terminal specific antibodies were detected in polyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Furthermore, Nter failed to induce cytotoxic effects on epithelial cells in cell medium of physiological pH. Currently many low pathogenic AIV strains do not express full-length PB1-F2 or express its C terminally truncated PB1-F2 form (PB1-F2 (1-52)) (12,38). Virus expression of truncated PB1-F2, which fails to induce cytotoxicity under physiological conditions, may be correlated to the viral fitness to prevent the deleterious cytotoxicity of the full-length PB1-F2.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Nter failed to induce cytotoxic effects on epithelial cells in cell medium of physiological pH. Currently many low pathogenic AIV strains do not express full-length PB1-F2 or express its C terminally truncated PB1-F2 form (PB1-F2 (1-52)) (12,38). Virus expression of truncated PB1-F2, which fails to induce cytotoxicity under physiological conditions, may be correlated to the viral fitness to prevent the deleterious cytotoxicity of the full-length PB1-F2.…”
Section: Discussionmentioning
confidence: 99%
“…However, both CN01 and CN02 had an S31N mutation in the M2 protein, which confers resistance to adamantine. No truncated PB1-F2, associated with increased virulence [26,27], was observed in CN01 and CN02. Aspartic acid at PB2 residue 701 (present in CN01 and CN02) is associated with reduced transmissibility [28].…”
Section: Environmental Samplesmentioning
confidence: 92%
“…A large amount of studies have also demonstrated that another accessory protein, PB1-F2, acts as a virulence regulatory factor in the pathogenesis of influenza virus. Multifunctional roles have been attributed to this protein, including inducing cell death, increasing pathogenesis and cytokine dysfunction, enhancing secondary bacterial pneumonia and so on [Reviewed in [85][86][87][88][89]. However, apparently the PA-X protein behaves in an opposite way by decreasing cell death, diminishing cytokine and inflammatory response and decreasing the pathogenicity of H5N1 and H1N1 influenza viruses [6,11,12,15] (see also Fig.…”
Section: Discussionmentioning
confidence: 99%